A Companion to Philosophy in Australia and New Zealand (Second Edition) - Oppy, Graham (Philosophy, 2014)
Philosophy in Australia and New Zealand has been experiencing something of a 'golden age'. Within this, the richness of Australasia's philosophical past, though less well known, should not be forgotten: Australasian philosophy includes much distinctive and highly original work. The Companion contains a wide range of articles by prominent philosophers and scholars, as well as important contributions by those outside academia. As well as longer essays on selected philosophers, philosophical topics and controversies, there are shorter entries on associations, research centres, departments, journals, pedagogy and international links. Philosophy's recent inroads into the wider community are also highlighted. A Companion to Philosophy in Australia and New Zealand provides scholars and the wider community with a greater appreciation of the philosophical heritage of this region, and will be a standard work of reference for many years to come. "Judicious and authoritative" - Graham Priest